Rancang Bangun Identity and Access Management IoT Berbasis KSI dan Permissioned Blockchain - Guntur Dharma Putra; Sujoko Sumaryono; Widyawan Widyawan (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2018)
Blockchain offers several technological break-throughs, ranging from monetary solutions to healthcare systems. Some approaches have proposed blockchain implementation in IoT for providing better performance and scalability. However, massive scale implementation of IoT devices suffers from several issues in identity and access managements of interconnected devices. The present study proposes the combination of permissioned blockchain and Keyless Signature Infrastructure (KSI) as a means of governing the identity and access management of IoT devices. KSI is known for its ability to offer digital signature services without the need of public or private key but hash trees updated in a regular basis. With the decentralization fashion of blockchain, KSI can be implemented more efficiently. The results may give an identity and access management with high scalability.